МОДЕЛЮВАННЯ МЕРЕЖІ НАДАННЯ ПУБЛІЧНИХ СЕРВІСІВ ТА ПОСЛУГ У СФЕРІ КУЛЬТУРИ ХАРКІВСЬКОЇ ОБЛАСТІ - Н. А. Плотнік (International Journal of Innovative Technologies in Social Science, 2020)
In the article the author considers the peculiarities of modeling the basic network of cultural institutions of local level in Kharkiv region, the use of scientific methods and approaches during modeling, identifies problems in ensuring the provision of quality cultural services by cultural institutions and services to local communities.